Browning inhibition and kinetics of fresh-cut bananas (cv. Lacatan) using carrageenan-based edible coatings - Guballa, Maria Carmela S.
ABSTRACT The effect of carrageenan-based edible coatings, with ascorbic acid (anti-browning agent) and citric acid (acidulant), in the browning of sliced bananas had been studied. Different coating solutions were prepared and bananas coated with the solutions were subjected to VQR analysis. The VQR results indicated that carrageenan-ascorbic acid coating with adjusted pH was the best to prevent browning. Kinetic profiles of enzymatic browning of treated and untreated bananas were found to be zero and first order reactions, respectively. During the storage study, significant changes in weights and color occurred between samples. The treated bananas showed less weight loss and higher L* and lower a* values compared to untreated ones. No significant changes in pH, titrable acidity and total soluble solids were evident between the treatments, but were evident across days. Results show that the combined effects of carrageenan as an oxygen barrier and the ascorbic acid as an antibrowning agent proved effective in delaying the onset of browning in sliced bananas.